Resection Prior to Liver Transplantation for Hepatocellular Carcinoma - Belghiti, Jacques (2003)
Objective: To evaluate the feasibility and postoperative course of liver transplantation (LT) in cirrhotic patients who underwent liver resection prior to LT for HCC. Summary Background Data: Although LT provides longer survival than liver resection for treatment of small HCCs, donor shortage and long LT wait time may argue against LT. The feasibility and survival following LT after hepatic resection have not been previously examined. Methods: Between 1991 and 2001, among 107 patients who underwent LT for HCC, 88 met Mazzafero’s criteria upon pathologic analysis of the explant. Of these, 70 underwent primary liver transplantation (PLT) and 18 liver resection prior to secondary liver transplantation (SLT) for recurrence (n = 11), deterioration of liver function (n = 4), or high risk for recurrence (n = 3). Perioperative and postoperative factors and long-term survival were compared. Results: Comparison of PLT and SLT groups at the time of LT revealed similar median age (53 vs. 55 years), sex, and etiology of liver disease (alcohol/viral B/C/other). In the SLT group, the mean time between liver resection and listing for LT was 20 months (range 1–84 months). Overall time on LT waiting list of the two groups was similar (3 vs. 5 months). Pathologic analysis after LT revealed similar tumor size (2.2 vs. 2.3 cm) and number (1.6 vs. 1.7). Perioperative and postoperative courses were not different in terms of operative time (551 vs. 530 minutes), blood loss (1191 vs. 1282 mL), transfusion (3 vs. 2 units), ICU (9 vs. 10 days) or hospital stay (32 vs. 31 days), morbidity (51% vs. 56%) or 30-day mortality (5.7% vs. 5.6%). During a median follow-up of 32 months (3 to 158 months), 3 patients recurred after PLT and one after SLT. After transplantation, 3- and 5-year overall survivals were not different between groups (82 vs. 82% and 59 vs. 61%). Conclusions: In selected patients, liver resection prior to transplantation does not increase the morbidity or impair long-term survival following LT. Therefore, liver resection prior to transplantation can be integrated in the treatment strategy for HCC.